Archetypical Analysis of Kagan Almis Epic - Senocak, Ebru; Dogan, Oguz (Geleneksel Yayincilik Ltd Stl, 2017)
Altai, located in the highlands in the south of Siberia, is a place where Shamanist beliefs are preserved with vitality. Epics, one of the most important narrative genres used by Altai Turkish people who accomplished narrating their centenary cultural experience in oral tradition, are the legacies which reflect common memory of people. Effecting nations deeply, and preserving cultural memory by being kept in minds, epics are of great importance in relation with national identity. Kagan Almis, the epic studied herein, is a substantially rich in respect to archetypes. In this article, we are going to try to define how the community found their way back to mythical origins by using Joseph Campbell's categorization as termed 'leaving-staging-returning sub-headings. The mythical items of the subconscious spirit constituting the epic is going to be examined in the light of archetypal symbolism;' furthermore, the rebirth of the society will be determined with the accumulation of the common consciousness's heritage of the cultural memory. The hero, who gets mature by going through some challenges, becomes the leader after experiencing a dramatic change. Besides, we are going to focus on heroic assets of the person who would lead the tribe, the communal struggle, and the importance of traditions in former Turkish society in the context of epic genre. For example, hero of the epic, Cilanas Uul, is a weak character in the beginning; then his character develops after he realizes his extraordinary and inborn powers, and becomes the leader of his people with the help of his challenging soul, which gams integrity with combining battle, courage and manliness with the God-given spiritual power. At the end of the epic, Cilanas Uul shines like a sun and gains power of government, complying with every requirements in epic genre. It could apparently understood that epics, a narration of the collective, have a common structure and function, and they signify important messages to the community. Epic heroes are the self-sacrificing types, who have assets idealized by their people. A hero, who is expected to realize dreams of people, has the right and power to deserve to be the leader of his people with his/her miraculousbirth, powers, comrades and arms. The hero in epic of Kagan Almis, Cilanas Uul, shows his readiness and courage by taking the road to his individualization. Passing the threshold, he overcomes the obstacles with success. He comes back, in a sense, is reborn, by getting mature and ascending the throne.
Almis kağan destani?in arketipsel tahlili
Keywords: Altai; Kagan Almis epic; Cilanas Uul; symbol; archetype